FEATURES OF THE APPLICATION OF THE MAIN DIAGRAMS OF ELECTRICAL CONNECTIONS OF MODERN NETWORKED WIND POWER PLANTS DURING THE SELECTION AND JUSTIFICATION OF THE MAIN CHARACTERISTICS OF THE WIND ELECTRIC PLANT FOR INTEGRATION IN THE WORK OF ELECTRICAL ENERGY ISSUE - SEGEDA, MYKHAILO; SIKORSKA, OLENA; DUDURYCH, OLEXANDRA; ROMANIV, STANISLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper discusses the application of main electrical connection schemes in modern power grids when choosing and justifying the key characteristics of wind power plants for integration into power systems. It describes modern wind power systems of various purposes and their classification based on the key parameters. The main components of wind power plants, their design, and purpose are considered. The research investigates the structure and features of electrical connections in modern grid-connected wind power plants. It describes eight different configurations of wind power plants with different types of generators, with and without a gearbox, with capacitors, with converters for partial and full-rated power of the generators. In the work, the selection and justification of the main characteristics of modern wind turbine systems for integration into the operation of electric power systems is carried out. With: a study of the specifics of the structural and functional composition of modern wind turbine systems was carried out. It was established that the degree of development and cost of power electronics will continue to play a key role in the selection of optimal schemes for the technical connection of WPPs to UES networks; conducted a study of the structure and features of the application of the main schemes of electrical connections of modern network wind power stations. It has been established that the main driving forces for the development of wind turbine technology can be the technical requirements of system operators for connecting wind turbines/wind turbines to the grid, as well as the cost of the electricity produced by them (including the reliability of wind turbines); the selection and substantiation of the main characteristics of modern systems of wind energy installations for integration into the operation of electric power systems was carried out. The structure, characteristics and component schemes of electrical connections of wind power plants are determined by the unit capacity of the wind power plant, their number, location on the terrain, and the type of used wind turbine power generation system. Depending on these parameters, the scheme of electrical connections of the wind turbine to the EM can be made according to the main, radial or mixed principle.